THE INFLUENCE OF ADVERTISING, PUBLICITY, AND PUBLIC RELATION ON CONSUMER PREFERENCE IN MANADO QUALITY HOTEL - Karema, Archie (Jurnal Berkala Ilmiah Efisiensi, 2016)
ABSTRACT A company must do more than make good products, they have to inform consumers about product benefits and carefully position their products in consumers’ mind. Recently, advertising, publicity and public relation are proved as effective moves by top companies to deliver their purpose as a main preference to all consumers. The study aim to find the influence among advertising, publicity, and public relation on consumer preference in Manado Quality Hotel. The research method is purposive analysis and the data is obtained from questionnaire that distributed to the consumer of Manado Quality Hotel. The analysis method is multiple regression analysis. 100 consumers of Manado Quality Hotel were randomly selected as samples. The result showed that Advertising, Publicity and Public Relation have a positive influence on consumer preference. However, Publicity is showed not significantly on consumer preference. The company should improve the quality of advertising and public relation as their marketing tools. Keywords : Advertising, Publicity, Public Relation, Consumer Preference.